2018
DOI: 10.1093/jac/dkx503
|View full text |Cite
|
Sign up to set email alerts
|

Defining the appropriateness and inappropriateness of antibiotic prescribing in primary care

Abstract: In English primary care, most antibiotics are prescribed for conditions that only sometimes require antibiotic treatment, depending on patient-specific indicators. Experts estimated low ideal prescribing proportions in many of these conditions. Incomplete prescribing guidelines and disagreement about prescribing in some conditions highlight further research needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 41 publications
1
74
2
1
Order By: Relevance
“…co-morbidity). 31 Our study does not account for this. It would be prudent, therefore, for future work to assess the appropriateness of antibiotic prescribing for GPs located in deprived areas.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…co-morbidity). 31 Our study does not account for this. It would be prudent, therefore, for future work to assess the appropriateness of antibiotic prescribing for GPs located in deprived areas.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…23 The ideal percentage rate for antibiotic prescription for acute bronchitis has currently been established at 13%. 24 Our study clearly shows that a single intervention fails to achieve this goal, since this percentage was not met either after the intervention or In conclusion, antibiotic prescription for LRTIs remained similar 6 years later among doctors exposed to the intervention, whereas control GPs prescribed significantly more antibiotics. However, the impact of the intervention was more intense 1-3 months after the intervention than 6 years later, since GPs assigned to the intervention group interpreted the CRP results differently 6 years later as they were less confident to withhold antibiotic therapy for patients with low CRP concentrations compared with what they did just after the intervention.…”
Section: Discussionmentioning
confidence: 59%
“…The ideal percentage rate for antibiotic prescription for acute bronchitis has currently been established at 13% . Our study clearly shows that a single intervention fails to achieve this goal, since this percentage was not met either after the intervention or 6 years later without any reminder.…”
Section: Discussionmentioning
confidence: 72%
“…A strength of our study is that we derived our tier classification using a more rigorous modified Delphi method. Two previous studies have derived ideal antibiotic prescribing rates for UK (21) and European (22) primary care settings. The appropriateness rates in those studies are shown and compared with the current consensus-defined Canadian appropriateness rates in Table 3.…”
Section: Discussionmentioning
confidence: 99%